2017
DOI: 10.21037/gs.2017.06.13
|View full text |Cite
|
Sign up to set email alerts
|

To identify or not to identify parathyroid glands during total thyroidectomy

Abstract: Hypoparathyroidism is one of the most common complications after total thyroidectomy and may impose a significant burden to both the patient and clinician. The extent of thyroid resection, surgical techniques, concomitant central neck dissection, parathyroid gland (PG) autotransplantation and inadvertent parathyroidectomy have long been some of the risk factors for postoperative hypoparathyroidism. Although routine identification of PGs has traditionally been advocated by surgeons, recent evidence has suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 51 publications
(77 reference statements)
0
40
0
3
Order By: Relevance
“…Visual identification of all four (or 3-4) in situ PGs for preservation during total thyroidectomy has traditionally been advocated by surgeons to lower the risk of hypoparathyroidism and hypocalcaemia (5,10). However, this approach may not guarantee…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Visual identification of all four (or 3-4) in situ PGs for preservation during total thyroidectomy has traditionally been advocated by surgeons to lower the risk of hypoparathyroidism and hypocalcaemia (5,10). However, this approach may not guarantee…”
Section: Discussionmentioning
confidence: 99%
“…Injury to RLNs, which provide motor innervation to the intrinsic muscles of the larynx, can lead to unilateral vocal cord paralysis characterized by inadequate coughing, inability to clear secretions, and aspiration in the postoperative setting (4) and may cause life-threatening airway obstruction. (3) Inadvertent damage or removal of the PGs during thyroid surgery can result in acute and chronic parathyroid insufficiency syndromes, especially postoperative hypocalcaemia, protracted hypoparathyroidism, and permanent hypoparathyroidism (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the rate of postoperative transient hypocalcemia ranges from 6% to 30%, although there is ≤2% incidence of persistent dysfunction. 7 The nadir of hypocalcemia often appears within 48 hours after thyroidectomy. 8 Symptoms are severe and, requiring calcium replacement therapy.…”
Section: Introductionmentioning
confidence: 99%